The economic dimension of US military assistance: security packages and their impact on Ukraine’s defense capability and financial sustainability - Yu.Yu. Moroz; A.A. Havrysh (Економіка, управління та адміністрування)
The article examines the economic dimension of US military assistance aimed at supporting Ukraine’s defense capabilities and stabilizing its financial system in the context of ongoing military aggression. Particular attention is paid to the analysis of the US security packages as an instrument of not only military but also economic support, including the supply of weapons, technical support for the Armed Forces of Ukraine and financial support for the defense budget. The study analyzes the structure of these packages, their role in strengthening Ukraine’s defense capabilities, and the economic consequences of receiving them. Security packages not only enhance the defense potential of the state, but also demonstrate the West’s support for Ukraine’s territorial integrity and sovereignty. This article analyzes the structure of these packages and identifies their role in strengthening Ukraine’s defense capabilities, their impact on Ukraine’s military capabilities, and long-term strategic implications for regional security. During 2014–2024, US military support increased significantly, covering a wide range of weapons, training, and logistics, which significantly strengthened Ukraine’s defense capabilities. An analysis of the data on security packages under the PDA and USAI programs shows their critical importance in strengthening the country’s defense capabilities. Taken together, these programs included the supply of modern weapons, such as HIMARS, Patriot, and Javelin systems, as well as the provision of critical materials and financial support. USAI focused on long-term support, including the purchase of new weapons, funding for the modernization of military infrastructure, and personnel training. In 2024, a record amount of assistance was provided under this program. The long-term effects of this support include strengthening international security, developing the defense industry, and stabilizing the Ukrainian economy.